A superhydrophobic magneto-flow system for semi-automated electrochemical detection of Salmonella Typhimurium in food samples utilizing an aptamer-based technique - Panphut, Wattana; Sangthong, Natthawut; Khamcharoen, Wisarut; Naorungroj, Sarida; Ngamrojanavanich, Nattaya; Srisa-Art, Monpichar; Ozer, Tugba; Wonsawat, Wanida; Chailapakul, Orawon; Jampasa, Sakda (ELSEVIER SCIENCE SA, 2026)
The existing methodologies for detecting foodborne pathogens often involve laborious and time-consuming procedures, underscoring the need for rapid and effective detection techniques. Herein, we present a super-hydrophobic magneto-flow system integrated with an electrochemical aptasensor designed for simple, sensitive, yet controlled detection of Salmonella enterica serovar Typhimurium (Salmonella) in food samples. A super-hydrophobic surface created through a chemical gold reduction method on a polydimethylsiloxane substrate enabled a distinct fluid orientation within a microfluidic device that prevents merging, thereby reducing contamination and enhancing detection rates. A laminate magneto-driven microfluidic device was fabricated using laser cutting and assembled to establish channel barriers that allow for precise control of magnetic flow direction using magnetic force, rather than relying on external pumps or absorbent pads. Aptamers specifically targeting Salmonella were conjugated to magnetic beads and aligned on the superhydrophobic surface with a custom-designed pattern to facilitate one-time spotting of the requisite reagents. Using a single introduced platform, the entire operation, including Salmonella-aptamer capturing, washing, and electrochemical measurement, can be performed sequentially, akin to a move-pause station. The aptasensing system operated in a label-free format, demonstrated the capability to detect Salmonella in food samples, achieving high sensitivity successfully (limit of detection = 10.01 CFU/mL), selectivity, a rapid response time (30 min), and a broad linearity range (10-105 CFU/mL), verified by standard approaches. This device embodies a cutting-edge immunosensing platform that facilitates precise operational control and features simple fabrication processes, rendering it a viable alternative suitable for complex multi-step procedures.
Keywords: Superhydrophobic device; Magneto-flow system; Aptasensor; Electrochemical detection; Salmonella enterica serovar Typhimurium; GRAPHENE; Chemistry; Electrochemistry; Instruments & Instrumentation